”Wielka Brytania, wielkie nadzieje”: reprezentacja polskiej migracji w Londyńczykach - Rydzewska, Joanna (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
Following the 2004 expansion of the European Union (EU), Polish migrant workers began arriving in the United Kingdom on an unprecedented scale. Londoners (Londyńczycy, 2008-9) was a response to this. Exploring the lives of Polish migrants in London, the series became an instant success on Polish television, regularly attracting around four million viewers. This article explores how Londoners represents Britishness and Polishness to its target Polish audience. It will argue that the series negotiates questions of Polish national identity, which over the past 20 years has been undergoing fundamental redefinition as a result of the ending of the Cold War and Poland’s accession to the EU.

Po rozszerzeniu Unii Europejskiej w 2004 roku, polscy migranci poszukujący pracy zaczęli przybywać do Wielkiej Brytanii na niespotykaną dotąd skalę. Serial Londyńczycy (2008-9) był odpowiedzią na to zjawisko. Opowiadający o życiu polskich migrantów w Londynie, serial ten stał się wielkim sukcesem polskiej telewizji, regularnie przyciągając około czterech milionów widzów. Artykuł analizuje, w jaki sposób brytyjskość oraz polskość reprezentowane są w Londyńczykach wobec docelowej polskiej publiczności. Główna teza zasadza się na twierdzeniu, że serial negocjuje kwestie polskiej tożsamości narodowej, która od dwudziestu lat przechodzi fundamentalną redefinicję, stanowiącą rezultat zakończenia zimnej wojny i przystąpienia Polski do Unii Europejskiej.
‘Great Britain, Great Expectations’: The Representation of Polish Migration to Great Britain in Londyńczycy/Londoners
Joanna Rydzewska, Swansea University, ”Wielka Brytania, wielkie nadzieje”: reprezentacja polskiej migracji w Londyńczykach, ‘Great Britain, Great Expectations’: The Representation of Polish Migration to Great Britain in Londyńczycy/Londoners, „Images” 2012, vol. XI: (Re)imagining the Past, red. A. Mrozewicz i J. Czaja, nr 20, s. 200-211., ISSN 1731-450X, język: polski
Keywords: Polish migration to the UK; national identity; European identity; transnational discourse; Polish television drama; Londoners; polska migracja do Wielkiej Brytanii; tożsamość narodowa; tożsamość europejska; dyskurs transnarodowy; polski serial telewizyjny; Londyńczycy